Galerkin Approach for Deflections on a Simply Supported Beam - Ragavi .V, Geetha. N. K, Bridjesh .P, Gomathi .M (International Journal of Advanced Science and Technology, 2019)
Galerkin method is quickly moving into the standard of science for the most part due to its applications in differing fields which incorporate structural building, science, electrical designing, activity look into (scheduling). In this paper we present the analysis of deflections on a simply supported beam using galerkin method and exact solution method As the amount of terms is extended in the acknowledged kind of Galerkin plan, it Methodologies are cautious worth monotonically. An answer with lesser number of terms addresses a stiffer system vis‐à‐vis a structure which has more terms. As number of terms increase, so does the versatility of the system. Therefore, precision of plan increases with number of terms.